Study of Social Enterprise Initiatives: nourishing innovation for global hunger - Tun Amir Adlan Tun Mohamad Ammar,; Ummi Darwisyah Ardini Shah Jahan,; Aisyah Hanani Anizan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The research focuses on the role of social enterprise initiatives in promoting innovation towards solving global problems, such as agricultural improvement and food security. Using qualitative analysis, case studies, and empirical data delves into how such enterprises offer innovative solutions to global problems. Highlighting adaptability and flexibility, the findings suggest the promising prospects of these ventures and provide recommendations for policymakers and stakeholders interested in sustainable development and global food security.